The relationship between adiposity parameters and C-reactive protein values in overweight and obese women - Mraović Tatjana; Radaković Sonja; Ristić-Medić Danijela; Dinčić Dragan; Tepšić-Ostojić Vesna; Čairović Aleksandra; Miljanović Gora; Rađen Slavica (Vojnosanitetski Pregled)
Background/Aim. Overweight/obesity has become important health problem in developed countries. It may be related to a presence of low-grade inflammation in white adipose tissue. The aim of this study was to investigate the levels of inflammatory marker C-reactive protein (CRP) and its relation to anthropometric parameters in overweight and obese females. Methods. This study included 200 apparently healthy, overweight and obese women (18–45 years). Their standard and alternative anthropometric parameters [body mass index (BMI), percentage of fat (%F), waist circumference (WC), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), body adiposity index (BAI)] were determined and correlated to serum CRP concentration. Results. Average CRP level was 5.56 ± 2.43 mg/L, and it significantly positively correlated to all investigated anthropometric parameters. There was significant difference between overweight and obese group in all investigated anthropometric parameters, as well as in CRP values. When investigated separately, according to BMI, values regarding obese females showed significant correlation between CRP and every investigated anthropometric parameter. In overweight subjects, no such correlation was recorded. In the obese group, all investigated parameters were significantly related to F. In overweight subjects, body weight (BW), BMI, WC and WHtR showed significant relation to F. Conclusion. The significant difference between the overweight and obese group in all parameters of central obesity was found as well as in the CRP levels. In the obese group, we found strong correlation between adiposity measured by fat percentage and parameters of central obesity, while in the overweight group WHR and BAI did not correlate to fat percentage. Our results confirmed that CRP is a valuable marker of metabolic risk in obese females, and BMI, although not so new, is still reliable parameter of adiposity.